A novel hollow Co3O4@N-doped carbon nanobubble film composite for high-performance anode of lithium-ion batteries. (1st November 2021) - Chen, Kaixiang; Huang, Run; Gu, Fengling; Du, Yan; Song, Yonghai
Abstract: Co3 O4 nanomaterials and their composites are replacing carbon as anode materials of lithium-ion batteries (LIBs) because of their large theoretical capacity, low cost and high abundance. However, the volume expansion in the process of charging/discharging leads to the destruction of Co3 O4 nanomaterials and thus results in poor cyclic stability, which limits their practical application seriously. Herein, a novel N-doped carbon nanobubble film (CNBF) with hollow Co3 O4 nanomaterials (H–Co3 O4 ) composites (H–Co3 O4 @CNBF) was prepared by proposing covalent-organic framework (COF) as template and carrier of Co 2+ . Using in-situ anchoring H–Co3 O4 strategy, a two-step calcination method was employed to prepare H–Co3 O4 @CNBF. The obtained H–Co3 O4 @CNBF exhibited a good lithium storage ability originated from anchored H–Co3 O4 nanomaterials and high cycle performance as the anode of LIBs came from the buffering of CNBF. The as-prepared H–Co3 O4 @CNBF showed excellent capacity of 808.0 mA h g −1 after 100 cycles at 0.2 A g −1 and outstanding cycle stability of 540.0 mA h g −1 after 200 cycles at 2 A g −1 . The combination of CNBF derived from COFs with H–Co3 O4 is a good strategy, which provides a new guide for the preparation of novel metal oxides and carbon composites. Graphical abstract: Image 1 Highlights: A novel N-doped carbon nanobubble film with hollow Co3 O4 was prepared by using covalent organic framework. The composites exhibit good Li  +  storage ability originated from anchored hollow Co3 O4 nanoparticles. The composites exhibit high cycle performance originated from N-doped carbon nanobubble film. This core-shell structure of composites can avoid the damage caused by volume expansion of Co3 O4 effectively.